2012
DOI: 10.1038/cddis.2012.83
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of argininosuccinate synthetase-1 sensitises lymphomas to arginine deiminase treatment, autophagy and caspase-dependent apoptosis

Abstract: Tumours lacking argininosuccinate synthetase-1 (ASS1) are auxotrophic for arginine and sensitive to amino-acid deprivation. Here, we investigated the role of ASS1 as a biomarker of response to the arginine-lowering agent, pegylated arginine deiminase (ADI-PEG20), in lymphoid malignancies. Although ASS1 protein was largely undetectable in normal and malignant lymphoid tissues, frequent hypermethylation of the ASS1 promoter was observed specifically in the latter. A good correlation was observed between ASS1 met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
131
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 26 publications
0
131
1
1
Order By: Relevance
“…In contrast, in the ASS1-methylated NMFH-1 cells, 5-aza-2 0 -deoxycytidine pretreatment failed to regain ASS1 expression irrespective of combined or separate use of EZH2 knockdown and various inhibitors against formation of repressive histone codes. This finding in NMFH-1 myxofibrosarcoma cells was not in keeping with the series of ASS1-methylated T-cell lymphoma cell lines, in which the ASS1 enzyme was readily reexpressed by demethylating agents (35). Our results indicated that a combination therapy of ADI-PEG20 and demethylating agents appears without effect in myxofibrosarcomas, a subset of which may use additional mechanism(s) other than DNA methylation and/or deregulated histone modifications to abolish ASS1 expression.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast, in the ASS1-methylated NMFH-1 cells, 5-aza-2 0 -deoxycytidine pretreatment failed to regain ASS1 expression irrespective of combined or separate use of EZH2 knockdown and various inhibitors against formation of repressive histone codes. This finding in NMFH-1 myxofibrosarcoma cells was not in keeping with the series of ASS1-methylated T-cell lymphoma cell lines, in which the ASS1 enzyme was readily reexpressed by demethylating agents (35). Our results indicated that a combination therapy of ADI-PEG20 and demethylating agents appears without effect in myxofibrosarcomas, a subset of which may use additional mechanism(s) other than DNA methylation and/or deregulated histone modifications to abolish ASS1 expression.…”
Section: Discussioncontrasting
confidence: 64%
“…However, the mechanistic underpinning responsible for suppression or reexpression of ASS1 is yet to be elucidated, especially in cancer tissues. Until recently, DNA methylation was identified as an inactivating mechanism of ASS1 expression only in pleural mesotheliomas, lymphomas, and ovarian carcinomas (27,29,35). Nevertheless, data for ASS1 methylation in hepatocellular carcinomas or melanomas are limited, despite being 2 of the best-known neoplasms devoid of ASS1 expression, with auxotrophy for arginine and sensitivity to ADI-PEG20 (20).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of ADI-PEG 20 was derived from leukemia cell line studies and prior publications. 21,23 Three days after treatment, cells were harvested and counted using a Vi-CELL Cell Viability Analyzer (Beckman).…”
Section: Methylation Of Ass1 Genementioning
confidence: 99%
“…The demethylating agent decitabine reexpressed ASS1 protein in 253J, UMUC-3, and T24 cells, confirming epigenetic silencing as a key mechanism involved in ASS1 inactivation in bladder cancer cells (data not shown; ref. 22).…”
Section: Methylated Ass1 Is Linked To Increased Proliferation and Invmentioning
confidence: 99%